Electrostatic coupling in MoS₂/CuInP₂S₆ Ferroelectric vdW heterostructures - Li, Ping (2022)
Ferroelectric van der Waals (vdW) heterostructure have recently emerged as a low-power, versatile device paradigm because it combines the great diversity of the 2D materials and the memory nature of ferroelectrics. The non-volatile field effect generated by the polarization bound charge is the pivotal factor for the device's performance. Unfortunately, microscopic studies on the interplay between polarization switching and electrostatic coupling at the heterojunction remain largely overlooked. Herein, the authors investigate the electrostatic coupling phenomena of vdW heterostructures consisting of semiconducting MoS2 and ferroelectric CuInP2S6. Significant charge injection accompanying the polarization reversal appears to be the governing field effect that modulates the electronic and photoluminescent properties of MoS2, as revealed by correlated ferroelectric domain, surface potential, and photoluminescence microscopies. Conversely, the photoactivity of the MoS2 also affects the polarization stability of CuInP2S6. This work provides direct microscopic insight into the mutual electrostatic interactions in vdW ferroelectric-semiconductor heterojunctions, which has broad implications for ferroelectric field-effect applications.